Delivery Timing, Out‐Of‐Pocket Maternity Costs, and Postpartum Care Utilization: An Instrumental Variable Analysis Among Commercially Insured Women - Rebecca A. Gourevitch; Jessica L. Cohen; Tara Shakley; Sung Min Park; Mary Beth Landrum; Meredith B. Rosenthal; Mark W. Friedberg; Anna D. Sinaiko (Health Services Research, 2026)
ABSTRACT Objective To examine whether out‐of‐pocket costs during pregnancy and delivery affect use of postpartum care. Study Setting and Design Because health insurance deductibles and limits reset annually, the timing of childbirth within that year quasi‐randomly assigns people to different levels of cost‐sharing during pregnancy+delivery versus postpartum. We use a novel instrumental variable approach that leverages this variation to analyze whether higher maternity spending due to delivering early in the plan year affects postpartum care utilization. The exposure is maternity out‐of‐pocket spending, and the instrument is whether the delivery was in the first three versus last 3 months of the enrollee's health plan year; the primary outcome is use of any outpatient care postpartum. We analyze maternity episodes among Blue Cross Blue Shield of Massachusetts enrollees who gave birth, 2019–2023. Data Sources and Analytic Sample Commercial health insurance enrollment and claims data for individuals with continuous enrollment during pregnancy, delivery, and 3‐months postpartum ( N = 51,337). Principal Findings Out‐of‐pocket costs for those delivering at the start versus the end of their health plan year were, on average, 21% higher for pregnancy+delivery care and 58% lower for postpartum care. A $100 increase in pregnancy+delivery out‐of‐pocket spending led to a 0.53 percentage point (95% CI [0.28, 0.79]) increase in use of any outpatient postpartum care (sample mean: 82.5%). Higher pregnancy+delivery out‐of‐pocket costs also led to significant increases in the number of outpatient contact days, visits for preventive/well care, visits for mental health, and other visits. Conclusions Higher pregnancy+delivery out‐of‐pocket costs due to delivering early in the plan year corresponded to lower postpartum out‐of‐pocket costs and led to modest increases in postpartum care. This suggests that lower postpartum cost‐sharing may increase postpartum care use. Policies that lower those costs may be effective in increasing use of postpartum care.